Mattering perception, work engagement and its relation to burnout amongst nurses during coronavirus outbreak - Salwa Ahmed Mohamed; Abdelaziz Hendy; Omaima Ezzat Mahmoud; Sayeda Mohamed Mohamed (Wiley, 2022)
Abstract Aim To assess the mattering perception, feelings of burnout and work engagement amongst nurses during coronavirus outbreak. Design Cross‐sectional research design. Methods It conducted at Zagazig fever hospital and chest hospital on 280 nurses. A self‐administered questionnaire containing four parts; characteristics, mattering at Work Scale, Burnout scale and Engagement scale. Results The present study reported that more than half of studied nurses had moderate mattering level and more than one‐quarter of them had low mattering. More than two‐fifth of studied nurses had moderate level and slight less than one‐third of them had low engagement. More than two‐fifth of studied nurses had moderate level of burnout, whilst slight less than one‐third of them had high burnout, and one‐quarter of them had low burnout.